Atrachinenynes A–D, four diacetylenic derivatives with unprecedented skeletons from the rhizomes of Atractylodes chinensis. (27th July 2022) - Chen, Fei-Long; Liu, Dong-Li; Fu, Jing; Fu, Lu; Gao, Jin; Bai, Li-Ping; Zhang, Wei; Jiang, Zhi-Hong; Zhu, Guo-Yuan
Abstract : Atrachinenynes A–D (1–4 ), four undescribed acetylenic derivatives with diverse skeletons, were isolated from Atractylodes chinensis . Abstract : Atrachinenynes A–D (1–4 ), four novel diacetylenic derivatives, were isolated for the first time from the rhizomes of Atractylodes chinensis . Compound 1 features a new C26 skeleton with an unusual 8/6/6/5 tetracyclic ring system bearing a diacetylene sidechain. Compounds 2–4 are three novel diacetylenic terpenoids with an additional six-membered ring between terpenes and diacetylenes formed via a Diels–Alder reaction. The structures and the absolute configurations of 1–4 were elucidated by spectroscopic methods, electronic circular dichroism (ECD) calculations, and 13 C quantum chemical calculations. Their plausible biogenetic pathways were also proposed.